2024
DOI: 10.1227/ons.0000000000001099
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study Evaluating the Comparative Effectiveness of Unilateral Hemilaminectomy and Bilateral Laminectomy in the Resection of Spinal Meningiomas

Wesam Said,
Emanuele Maragno,
Lara Leibrandt
et al.

Abstract: BACKGROUND AND OBJECTIVES: The primary treatment modality for spinal meningiomas (SM) is surgical resection. In recent years, minimal invasive spine surgery has gained considerable popularity, attributing its growth to advancements in surgical technologies and improved training of surgeons. Nonetheless, the suitability and effectiveness of minimal invasive spine surgery for intradural spinal tumor resection remain a subject of debate. In this cohort study, we aimed to compare the extent of resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…GTR was achieved in 93.84% of all cases included in this study. Moreover, previous publications comparing both approaches show significantly less blood loss and lower LOS [11]. More invasive surgical approaches do not seem to be required in most cases, even in ventral located and calcified meningiomas [11,27,39,40], and other intradural tumors [41].…”
Section: Minimal Invasive Surgerymentioning
confidence: 86%
See 2 more Smart Citations
“…GTR was achieved in 93.84% of all cases included in this study. Moreover, previous publications comparing both approaches show significantly less blood loss and lower LOS [11]. More invasive surgical approaches do not seem to be required in most cases, even in ventral located and calcified meningiomas [11,27,39,40], and other intradural tumors [41].…”
Section: Minimal Invasive Surgerymentioning
confidence: 86%
“…Moreover, previous publications comparing both approaches show significantly less blood loss and lower LOS [11]. More invasive surgical approaches do not seem to be required in most cases, even in ventral located and calcified meningiomas [11,27,39,40], and other intradural tumors [41]. Furthermore, minimal invasive unilateral approaches seem to play a role in preventing CSF leakage, one of the more frequent possible complications of after surgery on intra-dural pathologies [20,22,42,43].…”
Section: Minimal Invasive Surgerymentioning
confidence: 92%
See 1 more Smart Citation
“…GTR was achieved in 93.84% of all cases included in this study. Moreover, previous publications comparing both approaches show significantly less blood loss and lower LOS [11]. More invasive surgical approaches do not seem to be required in most cases, even in ventral-located and calcified meningiomas [11,28,36,41] and other intradural tumors [42].…”
Section: Minimal-invasive Surgerymentioning
confidence: 87%
“…Recently, we demonstrated that the resection of spinal meningiomas is feasible via a less invasive unilateral approach, showing a similar rate of gross total resection (GTR) in comparison to a bilateral laminectomy. Furthermore, we demonstrated that patients undergoing unilateral hemilaminectomy, with less muscle detachment and bone resection, had significantly less blood loss (EBL) during the surgical procedure and faster recovery with significantly shorter length of hospital stay (LOS) [11]. Minimalinvasive spine surgery (MISS) can further improve surgical outcomes through reduced surgical impact, decreased pain, and quicker recovery [12][13][14].…”
Section: Introductionmentioning
confidence: 99%